2013
DOI: 10.4172/2167-0277.1000111
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Practitioners (NPs) as Cognitive Behavioral Treatment for Insomnia (CBT-I) Providers: An Underutilized Resource

Abstract: Cognitive Behavioral Therapy for Insomnia (CBT-I) is an effective treatment for chronic insomnia, but it remains underutilized. Lack of appropriately-trained CBT-I providers is a major reason. Nurse Practitioners (NPs) may, in addition to psychologists, be uniquely positioned to fill this role, based not only on their professional training but also given a handful of studies showing these individuals' care outcomes meet or exceed standard outcomes. Questions as to how to attract NPs to the field, credential th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Although BBTi could potentially be delivered via a combination of GP and practice nurse appointments, GP-administered treatment sessions with practice nurse support may be more viable given the limited funding available for nursing consultations within the Medicare Benefits Schedule. 20,32 Practice nurses can assist GPs to review information about a patient's health history, insomnia symptoms and questionnaire and sleep-diary data; help to develop patientcentred goals for care; and provide education to patients. BBTi is suited to in-person and telephone appointments, and may be provided to individuals or in small-group settings.…”
Section: A Step-by-step Approach To Brief Behavioural Treatment For Insomniamentioning
confidence: 99%
See 1 more Smart Citation
“…Although BBTi could potentially be delivered via a combination of GP and practice nurse appointments, GP-administered treatment sessions with practice nurse support may be more viable given the limited funding available for nursing consultations within the Medicare Benefits Schedule. 20,32 Practice nurses can assist GPs to review information about a patient's health history, insomnia symptoms and questionnaire and sleep-diary data; help to develop patientcentred goals for care; and provide education to patients. BBTi is suited to in-person and telephone appointments, and may be provided to individuals or in small-group settings.…”
Section: A Step-by-step Approach To Brief Behavioural Treatment For Insomniamentioning
confidence: 99%
“…Evidence indicates that practice nurses can provide effective non-medication insomnia management within the primary care setting, to relieve the burden on GPs while supporting the adoption of guideline recommendations. 7,20,32 A recent Australian qualitative study also found that practice nurses are interested in becoming more involved in the management of sleep disorders in general practice (eg insomnia and sleep apnoea). 37…”
Section: Role Of Practice Nurses In Bbtimentioning
confidence: 99%
“…A typical course of CBT-I is delivered to a patient across 4-8 weekly sessions although many alternative formats and delivery strategies have demonstrated efficacy (e.g., internetdelivered, group therapy, abbreviated treatment). Evidence suggests in addition to clinical psychologists and psychiatrists, nurse practitioners (30) and masters-level clinicians (31) can be trained to deliver CBT-I effectively making it a versatile, flexible intervention. However, uptake of CBT-I is low due to numerous barriers including limited patient and provider awareness of the intervention and lack of trained providers (32).…”
Section: Cognitive-behavioral Therapy For Insomniamentioning
confidence: 99%
“…[6] These approaches were devised to address the problem of large number of patients, who require several sessions; while there are a limited number of trained psychologists. [78]…”
Section: Introductionmentioning
confidence: 99%